Effects of Cyclosporine and Azacitidine on Some Hematologic and ‎Biochemical Parameters of Benzene-Induced Aplastic Anemia in Rats - Taher, Ghanem; F Hasn, Huda (The Iraqi Journal of Veterinary Medicine, 2023)
Aplastic anemia, marked by deficiencies in hematopoietic stem cells, leads to peripheral blood pancytopenia and hypocellular bone ‎marrow. This study aimed to evaluate the therapeutic efficacy of cyclosporine and azacitidine, administered either alone or in combination, in rats with benzene-induced aplastic ‎anemia, focusing on restoring normal blood cell levels and preventing disease complications. Thirty adult female Wistar rats ‎(Rattus ‎norvegicus)‎ were randomly divided into five groups: negative control (C-, untreated), positive control (C+, induced aplastic anemia with ‎distilled water), cyclosporine-treated (CsA, 5.86 mg/kg), azacitidine-treated (Aza, 5.75 mg/kg), and combination-treated (CsA+Aza, 3.68 ‎mg/kg each). Benzene (1940 mg/kg) was administered orally for fifteen days to induce aplastic anemia. Post a 30-day treatment period, ‎evaluations included differential WBC and reticulocyte counts, serum IL-2 levels, and alkaline phosphatase (ALP) activity. Results ‎showed significant improvements in WBC% and reticulocyte% in all treated groups compared to the C+ group, with the combination-‎treated group showing the highest enhancement. IL-2 levels in the combination group were significantly reduced compared to other ‎treatment groups, aligning closely with the negative control. The ALP activity was significantly higher in both the cyclosporine and ‎azacitidine-treated groups compared to the positive control, with the combination group showing a marked increase over the azacitidine ‎group but no significant difference from the cyclosporine group and negative control.‎ In conclusion, the study demonstrates the potential therapeutic benefits of cyclosporine and azacitidine in treating benzene-induced ‎aplastic anemia in rats. The combination therapy, in particular, showed improved efficacy in all tested parameters, suggesting a potential ‎strategy for dose reduction and toxicity mitigation.